Perlindungan Konsumen dalam Transaksi E-Commerce Perspektif Hukum Ekonomi Syariah - Ahlan Ahlan (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Consumer protection in e-commerce transactions is an increasingly important issue in line with technological advancements and the growing number of online transactions. In the context of Islamic economic law, this protection not only focuses on legal aspects but also emphasizes the ethical and moral values prescribed in Islam. This study aims to explore the concept of consumer protection in e-commerce from the perspective of Islamic economic law, as well as the urgency of regulation and education needed to create a safe and fair transactional environment.